Method for producing quantum dot and quantum dot

A core-shell structured quantum dot manufacturing method with a ZnSeS intermediate layer and controlled shell thickness addresses copper residue and shape issues, enhancing EQE and QY, resulting in efficient blue fluorescence.

JP2025020333AActive Publication Date: 2025-02-12TOPPAN HOLDINGS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024195063
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2024-11-07
Publication Date
2025-02-12
Estimated Expiration
2042-02-25

AI Technical Summary

Technical Problem

Existing methods for producing cadmium-free quantum dots with high external quantum efficiency (EQE) and narrow fluorescence half-width are hindered by issues such as copper residue, non-uniform shell thickness, and particle shape deterioration, leading to reduced light emission efficiency.

Method used

A core-shell structure with an intermediate ZnSeS layer and a controlled shell thickness is achieved by using a two-step coating process, incorporating acidic compounds and zinc halide compounds to enhance quantum yield (QY) and prevent Förster resonance energy transfer (FRET).

Benefits of technology

The method produces quantum dots with improved EQE of at least 7% and QY of 70% or more, achieving narrow fluorescence half-widths of 20 nm or less, suitable for blue fluorescence applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020333000001_ABST
    Figure 2025020333000001_ABST
Patent Text Reader

Abstract

To provide a method for producing a quantum dot capable of enhancing EQE, and the quantum dot.SOLUTION: The quantum dot of the present invention is a core-shell structure quantum dot. The shell has an intermediate layer and an outermost layer, the intermediate layer is located between the core and the outermost layer, and the intermediate layer contains ZnSeS and a halogen element. Preferably, at least, the external quantum efficiency is 7% or more or the fluorescence quantum yield is 70% or more.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing cadmium-free core-shell quantum dots, and to the quantum dots. [Background technology]

[0002] Quantum dots emit fluorescence and are also called fluorescent nanoparticles because their size is on the nanometer order, semiconductor nanoparticles because their composition is derived from semiconductor materials, or nanocrystals because they have a specific crystal structure.

[0003] The performance of quantum dots can be expressed by the fluorescence quantum yield (QY) and the external quantum efficiency (EQE).

[0004] When photoluminescence (PL) is used as the light emission principle for quantum dot displays, a method is used in which a blue LED is used as the backlight to generate excitation light, and quantum dots are used to convert it into green or red light. On the other hand, when electroluminescence (EL) is used as the light emission principle, or when quantum dots are used to emit all three primary colors in other ways, blue fluorescent quantum dots are required.

[0005] Cadmium selenide (CdSe) quantum dots that use cadmium (Cd) are representative of blue quantum dots. However, Cd is internationally regulated, and there have been high barriers to the practical application of materials using CdSe quantum dots.

[0006] On the other hand, the development of quantum dots that do not use Cd is also being considered. For example, CuInS 2 , AgInS 2Development of chalcopyrite quantum dots such as those described above and indium phosphide (InP) quantum dots is progressing (see, for example, Patent Document 1). However, the currently developed quantum dots generally have a wide fluorescence half-width and are not suitable as blue fluorescent quantum dots.

[0007] In addition, Non-Patent Document 1 listed below describes in detail a method for directly synthesizing ZnSe using diphenylphosphine selenide, which is considered to have a relatively high reactivity with organic zinc compounds, but is not suitable for use as blue fluorescent quantum dots.

[0008] Also, a method for synthesizing ZnSe in an aqueous system is reported in the following Non-Patent Document 2. Although the reaction proceeds at low temperatures, the fluorescence half-width is somewhat broad at 30 nm or more, and the fluorescence wavelength is less than 430 nm, making it unsuitable for use as a replacement for conventional blue LEDs to achieve a wide color gamut.

[0009] In addition, the following Non-Patent Document 3 reports a method of synthesizing ZnSe-based quantum dots by forming a precursor such as copper selenide (CuSe) and then cation-exchanging copper with zinc (Zn). However, since the particles of the precursor copper selenide are as large as 15 nm and the reaction conditions for cation-exchanging copper and zinc are not optimal, it can be seen that copper remains in the ZnSe-based quantum dots after cation exchange. From the results of the study of the present invention, it has been found that ZnSe-based quantum dots with residual copper cannot emit light. Alternatively, if copper remains even after emitting light, the emission will be due to defects, and the half-width of the emission spectrum will be 30 nm or more. The particle size of the precursor copper selenide also affects this copper residue, and if the particles are large, copper is likely to remain even after cation exchange, and even if ZnSe can be confirmed by XRD, it is often the case that light does not emit due to a small amount of residual copper. Therefore, Non-Patent Document 3 is cited as an example in which copper remains because the particle size of this precursor and the cation exchange method cannot be optimized. Therefore, blue fluorescence has not been reported. Although there are many reports of the cation exchange method, there are no reports of strong luminescence for the reasons mentioned above. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2007 / 060889 Brochure [Non-patent literature]

[0011] [Non-Patent Document 1] Organic Electronics 15 (2014) 126-131 [Non-Patent Document 2] Materials Science and Engineering C 64 (2016) 167-172 [Non-Patent Document 3] J. Am. Chem. Soc.(2015)137 29 9315-9323 Summary of the Invention [Problem to be solved by the invention]

[0012] Incidentally, the external quantum efficiency is calculated by the following formula (1). External quantum yield (EQE) = Carrier balance × Emission exciton generation efficiency × Emission quantum efficiency (fluorescence quantum yield (QY)) × Light extraction efficiency (Equation 1)

[0013] Here, the light extraction efficiency is generally 0.2 to 0.3, so if the carrier balance, the generation efficiency of luminescent excitons, and the fluorescence quantum yield are all 1 (100%), the theoretical external quantum yield is 20 to 30%. Therefore, in order to obtain a high EQE, quantum dots with a high QY are required.

[0014] In addition, if the quantum dots are too close to each other, Förster resonance energy transfer (FRET) occurs. As a result, the EQE decreases. Therefore, by using a core-shell structure in which the core is covered with a shell, the distance between the cores can be physically increased, and FRET can be reduced.

[0015] However, it has not been possible to mass-produce quantum dots that can cover the entire circumference of the core with a shell having a uniform thickness and have a high QY. For example, it has been found that increasing the shell thickness deteriorates the particle shape and decreases the QY accordingly. Therefore, the present invention has been made in consideration of the above-mentioned points, and an object of the present invention is to provide a method for producing quantum dots that can improve EQE, and quantum dots. [Means for solving the problem]

[0016] The quantum dot of the present invention is a quantum dot having a core-shell structure, the shell having an intermediate layer and an outermost layer, the intermediate layer being located between the core and the outermost layer, and the intermediate layer containing ZnSeS and containing a halogen element.

[0017] In the present invention, it is preferable that the external quantum efficiency is at least 7% or more, or the fluorescence quantum yield is at least 70%.

[0018] In the present invention, the halogen element is detected by elemental analysis using energy dispersive X-ray analysis, and the content of the halogen element is preferably 0.01 atom % to 5 atom %.

[0019] In the present invention, the halogen element is preferably chlorine or bromine. In the present invention, Cu may be contained.

[0020] The method for producing quantum dots according to the present invention is a method for producing quantum dots having a core-shell structure, wherein the shell has an intermediate layer and an outermost layer, the intermediate layer is located between the core and the outermost layer, and the step of producing the shell includes a step of coating the core with ZnSeS as the intermediate layer, and a step of blending an acidic compound and a zinc halide compound into the outermost layer. In the present invention, it is preferable to divide the step of coating the outermost layer into at least a first half and a second half, the first half including a step of blending the acidic compound but not blending the zinc halide compound, and the second half including a step of blending both the acidic compound and the zinc halide compound.

[0021] In the present invention, it is preferable to use at least one of hydrogen chloride, hydrogen bromide, and trifluoroacetic acid as the acidic compound, and it is preferable to use at least one of zinc chloride and zinc bromide as the zinc halide compound. Effect of the Invention

[0022] According to the method for producing quantum dots of the present invention, quantum dots having a good particle shape can be synthesized, the QY can be improved, and ultimately, a high EQE can be obtained. [Brief description of the drawings]

[0023] [Figure 1] 1A and 1B are schematic diagrams of quantum dots in an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of an LED device using quantum dots according to an embodiment of the present invention. [Diagram 3] 1 is a vertical sectional view of a display device using an LED device according to an embodiment of the present invention. [Figure 4] FIG. 2 is a flow chart illustrating a manufacturing process of quantum dots according to an embodiment of the present invention. [Diagram 5] 1 is a photoluminescence (PL) spectrum of Example 1. [Figure 6]1 is an absorption spectrum of Example 1. [Figure 7] FIG. 1 is an X-ray diffraction (XRD) spectrum of Example 1. [Figure 8] 1 is a table showing the measurement results of each quantum dot of Examples 1 to 7. [Figure 9] FIG. 9A is a photograph showing the TEM-EDX analysis results in Comparative Example 1, and FIG. 9B is a photograph showing the TEM-EDX analysis results in Example 1. [Figure 10] FIG. 10A is a partial schematic view of FIG. 9A, and FIG. 10B is a partial schematic view of FIG. 9B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] An embodiment of the present invention (hereinafter, abbreviated as "embodiment") will be described in detail below. Note that the present invention is not limited to the following embodiment, and can be practiced in various modifications within the scope of the gist of the present invention.

[0025] 1A and 1B are schematic diagrams of quantum dots in this embodiment. The quantum dots 5 shown in Fig. 1A and 1B are nanocrystals that do not contain cadmium (Cd). "Nanocrystal" refers to nanoparticles having a particle size of about several nm to several tens of nm. In this embodiment, a large number of quantum dots 5 can be generated with a substantially uniform particle size.

[0026] In this embodiment, the quantum dot 5 has a core-shell structure consisting of a core 5a and a shell 5b that covers the surface of the core 5a. The core 5a is preferably a nanocrystal containing at least zinc (Zn) and selenium (Se). The core 5a may also contain tellurium (Te) or sulfur (S). However, it is preferable that the core 5a does not contain cadmium (Cd) or indium (In).

[0027] Similarly to the core 5a, the shell 5b covering the surface of the core 5a also preferably does not contain cadmium (Cd) or indium (In). In this embodiment, the shell 5b contains a large amount of zinc (Zn). Specifically, the shell 5b is preferably made of zinc sulfide (ZnS), zinc selenide (ZnSe), or zinc sulfide selenide (ZnSeS). Of these, ZnS is preferable. The shell 5b may be in a state of being solid-dissolved on the surface of the core 5a. In this embodiment, by adopting a core-shell structure, a further increase in the fluorescence quantum yield (QY) can be expected while keeping the fluorescence half-width narrow.

[0028] In the quantum dot 5 of this embodiment, the entire surface of the core 5a can be covered with a shell 5b of ZnS or the like to a predetermined thickness. An intermediate layer may be interposed between the core 5a and the shell 5b. For example, this intermediate layer may be the first layer of the shell, that is, the shell 5b may have a structure of two or more layers. As an example, the shell 5b may have a layered structure made of ZnSeS / ZnS.

[0029] The quantum dot 5 may have a circular cross section as shown in FIG. 1A, or a polygonal cross section as shown in FIG. 1B. In the case of a polygonal shape, for example, a substantially rectangular shape or a substantially triangular shape is preferable. In this embodiment, the core 5a of the quantum dot 5 preferably contains at least Zn and Se, and thus the core 5a constituting the quantum dot 5 is easily formed into a polyhedron (for example, a substantially cubic shape) by crystal growth. That is, in this embodiment, the quantum dot 5 can be formed in a good shape with a uniform particle shape, rather than an indefinite shape. In this embodiment, the shell 5b can be formed with a substantially constant thickness around the entire circumference of the core 5a. Although not limited thereto, the shell 5b can be formed with a thickness of about 0.5 mm to 3 mm, preferably 1 mm or more and 2.5 mm or less. This is due to the incorporation of an acidic compound into the shell raw material, as described in the manufacturing method described later. In addition, in this embodiment, a zinc halide compound is incorporated into the shell raw material, which can improve the QY.

[0030] As shown in Figures 1A and 1B, it is preferable that a large number of organic ligands 11 are coordinated to the surface of the quantum dots 5. This makes it possible to suppress the aggregation of the quantum dots 5, and to develop the desired optical properties. Furthermore, by adding an amine or thiol-based ligand, it is possible to greatly improve the stability of the quantum dot emission properties. The ligands that can be used in the reaction are not particularly limited, but the following ligands are representative examples. (1) Aliphatic primary amines Oleylamine: C 18 H 35 NH 2 , Stearyl (octadecyl)amine: C 18 H 37 NH 2 , dodecyl(lauryl)amine: C 12 H 25 NH 2 , Decylamine: C 10 H 21 NH 2 , Octylamine: C 8 H 17 NH 2 (2) Fatty acid type Oleic acid: C 17 H 33 COOH, stearic acid: C 17 H 35 COOH, Palmitic acid: C 15 H 31 COOH, myristic acid: C 13 H 27 COOH, lauric acid: C 11 H 23 COOH, decanoic acid: C 9 H 19 COOH, octanoic acid: C 7 H 15 COOH (3) Thiols Octadecanethiol: C 18 H 37 SH, hexadecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C 8 H 17 SH (4) Phosphine-based Trioctylphosphine: (C 8 H 17 ) 3 P, triphenylphosphine: (C 6 H 5 ) 3 P, tributylphosphine: (C 4 H 9 ) 3 P (5) Phosphine oxides Trioctylphosphine oxide: (C 8 H 17 ) 3 P=O, triphenylphosphine oxide: (C 6 H 5 ) 3 P=O, tributylphosphine oxide: (C 4 H 9 ) 3 P=O (6) Alcohol-based Oleyl alcohol: C 18 H 36 O

[0031] It is also preferable that inorganic ligands are coordinated together with organic ligands. This makes it possible to suppress surface defects on the quantum dots and to develop higher optical properties. The ligands are not particularly limited, but halogens such as F, Cl, Br, and I are typical examples.

[0032] In the quantum dots 5 in this embodiment, elemental analysis by energy dispersive X-ray spectroscopy (EDX) has revealed that halogen elements are also detected in addition to Zn, Se, and S. The halogen element is preferably chlorine (Cl) or bromine (Br).

[0033] The content of the halogen element is not limited, but is sufficiently smaller than Zn, Se, and S, and is about 0.01 atom% to 5 atom%. The content of the halogen element is preferably about 0.5 atom% or more and 2 atom% or less. "Atom%" is a ratio when the number of all atoms constituting the quantum dot 5 is set to 100. The amount of the halogen element can be measured by EDX analysis.

[0034] In a quantum dot light-emitting diode (QLED) using the quantum dots 5 of this embodiment, the external quantum efficiency (EQE) can be effectively improved. In this embodiment, the EQE can be 7% or more. Preferably, the EQE can be 9% or more, more preferably, the EQE can be 9.5% or more, even more preferably, the EQE can be 10% or more, and even more preferably, the EQE can be 10.5% or more. The EQE can be evaluated using an LED measuring device and is determined as a maximum value.

[0035] Furthermore, as shown in the above formula (1), the EQE can be improved by increasing the QY. Therefore, in order to obtain a high EQE, it is preferable to increase the QY of the quantum dots 5. In this embodiment, the QY can be made 70% or more, preferably 75% or more, more preferably 80% or more, even more preferably 85% or more, even more preferably 90% or more, and most preferably 95% or more.

[0036] The quantum dots 5 of this embodiment preferably have a fluorescence half-width of 20 nm or less. The "fluorescence half-width" refers to the full width at half maximum, which indicates the spread of the fluorescence wavelength at half the intensity of the peak value of the fluorescence intensity in the fluorescence spectrum. The fluorescence half-width is more preferably 15 nm or less. In this way, in this embodiment, the fluorescence half-width can be narrowed, thereby improving the color gamut.

[0037] In this embodiment, as described later, in the reaction system for synthesizing the quantum dots 5, a copper chalcogenide is synthesized as a precursor, and then a metal exchange reaction is performed on the precursor. By producing the quantum dots 5 based on such an indirect synthesis reaction, it is possible to narrow the fluorescence half-width.

[0038] In addition, in this embodiment, the fluorescence lifetime of the quantum dots 5 can be set to 50 ns or less. Alternatively, in this embodiment, the fluorescence lifetime can be adjusted to 40 ns or less, 30 ns or less, or even 20 ns or less. In this way, in this embodiment, the fluorescence lifetime can be shortened, but can also be extended to about 50 ns, and the fluorescence lifetime can be adjusted depending on the application.

[0039] In this embodiment, the fluorescence wavelength can be freely controlled to about 410 nm or more and 470 nm or less. Specifically, the quantum dots 5 in this embodiment are solid solutions based on ZnSe. In this embodiment, the fluorescence wavelength can be controlled by adjusting the particle size of the quantum dots 5 and the composition of the quantum dots 5. In this embodiment, the fluorescence wavelength can be preferably set to 430 nm or more, and more preferably set to 440 nm or more. In this way, the quantum dots 5 of this embodiment can control the fluorescence wavelength to blue.

[0040] Next, a method for producing the quantum dots 5 of this embodiment will be described. The method for producing the quantum dots 5 of this embodiment includes a step of generating a core and a step of coating the surface of the core with a shell, and the step of coating the shell is characterized in that an acidic compound and a zinc halide compound are mixed into the shell raw material.

[0041] <Core synthesis method> A method for synthesizing the core will be described. First, in this embodiment, a copper chalcogenide precursor is synthesized from an organic copper compound or an inorganic copper compound and an organic chalcogen compound. Specifically, the copper chalcogenide precursor is Cu 2 Se, Cu 2 SeS, Cu2 SeTe, Cu 2 SeTeS is preferred.

[0042] Here, in this embodiment, the Cu raw material is not particularly limited, but for example, the following organic copper reagents or inorganic copper reagents can be used. That is, as acetates, copper acetate (I): Cu(OAc), copper acetate (II): Cu(OAc), 2 , as fatty acid salt, copper stearate: Cu(OC(=O)C 17 H 35 ) 2 , Copper oleate: Cu(OC(=O)C 17 H 33 ) 2 , Copper myristate: Cu(OC(=O)C 13 H 27 ) 2 , Copper dodecanoate: Cu(OC(=O)C 11 H 23 ) 2 , Copper acetylacetonate: Cu(acac) 2 Both monovalent and divalent compounds can be used as halides, such as copper(I) chloride: CuCl, copper(II) chloride: CuCl 2 , copper(I) bromide:CuBr, copper(II) bromide:CuBr 2 , Copper(I) iodide: CuI, Copper(II) iodide: CuI 2 etc. can be used.

[0043] In this embodiment, the Se raw material is an organic selenium compound (organic chalcogenide). The structure of the compound is not particularly limited, but for example, trioctylphosphine selenide: (C 8 H 17 ) 3 P=Se, or tributylphosphine selenide obtained by dissolving Se in tributylphosphine: (C 4 H 9 ) 3P=Se, etc. can be used. Alternatively, a solution in which Se is dissolved at high temperature in a high boiling point solvent such as a long chain hydrocarbon like octadecene (Se-ODE), or a solution in which Se is dissolved in a mixture of oleylamine and dodecanethiol (Se-DDT / OLAm) can be used.

[0044] In this embodiment, Te is used as a raw material in the form of an organic tellurium compound (organic chalcogen compound). The structure of the compound is not particularly limited, but for example, trioctylphosphine telluride (C 8 H 17 ) 3 P = Te, or tributylphosphine telluride obtained by dissolving Te in tributylphosphine: (C 4 H 9 ) 3 P=Te, etc. can be used. Also, diphenyl ditelluride: (C 6 H 5 ) 2 Te 2 Dialkyl ditellurides such as: R 2 Te 2 It is also possible to use

[0045] In this embodiment, an organic copper compound or an inorganic copper compound is mixed with an organic chalcogen compound and dissolved. As the solvent, octadecene can be used as a high boiling point saturated hydrocarbon or unsaturated hydrocarbon. In addition, t-butylbenzene can be used as an aromatic high boiling point solvent, and butyl butyrate can be used as an ester solvent with a high boiling point. 4 H 9 COOC 4 H 9 , benzyl butyrate: C 6 H 5 CH 2 COOC 4 H 9 It is also possible to use an aliphatic amine-based or fatty acid-based compound, an aliphatic phosphorus-based compound, or a mixture thereof as the solvent.

[0046] At this time, the copper chalcogenide precursor is synthesized at a reaction temperature set in the range of 140° C. to 250° C. Note that the reaction temperature is preferably lower, 140° C. to 220° C., and more preferably lower, 140° C. to 200° C.

[0047] In this embodiment, the reaction method is not particularly limited, but in order to obtain quantum dots with a narrow fluorescence half-width, Cu with uniform particle size is used. 2 Se, Cu 2 SeS, Cu 2 SeTe, Cu 2 It is important to synthesize SeTeS.

[0048] Next, an organic zinc compound or an inorganic zinc compound is prepared as a raw material for ZnSe, ZnSeS, ZnSeTe, or ZnSeTeS. The organic zinc compound or the inorganic zinc compound is a raw material that is stable even in air and easy to handle. Although there is no particular limitation on the structure of the organic zinc compound or the inorganic zinc compound, it is preferable to use a zinc compound with high ionicity in order to efficiently carry out the metal exchange reaction. For example, the organic zinc compound or the inorganic zinc compound shown below can be used. That is, zinc acetate: Zn(OAc) as an acetate salt. 2 , Zinc nitrate: Zn(NO 3 ) 2 , as fatty acid salt, zinc stearate: Zn(OC(=O)C 17 H 35 ) 2 , Zinc oleate: Zn(OC(=O)C 17 H 33 ) 2 , Zinc palmitate: Zn(OC(=O)C 15 H 31 ) 2 , Zinc myristate: Zn(OC(=O)C 13 H 27 ) 2 , zinc dodecanoate: Zn(OC(=O)C 11 H 23 ) 2 , Zinc acetylacetonate: Zn(acac) 2 , as a halide, zinc chloride: ZnCl 2, Zinc bromide: ZnBr 2 , zinc iodide: ZnI 2 , Zinc diethyldithiocarbamate as zinc carbamate: Zn(SC(=S)N(C 2 H 5 ) 2 ) 2 , zinc dimethyldithiocarbamate: Zn(SC(=S)N(CH 3 ) 2 ) 2 , zinc dibutyldithiocarbamate: Zn(SC(=S)N(C 4 H 9 ) 2 ) 2 etc. can be used.

[0049] Next, the organic zinc compound or inorganic zinc compound is added to the reaction solution in which the copper chalcogenide precursor is synthesized. This causes a metal exchange reaction between Cu of the copper chalcogenide and Zn. The metal exchange reaction is preferably caused at a temperature of 150°C or higher and 300°C or lower. It is also more preferable to cause the metal exchange reaction at a lower temperature, 150°C or higher and 280°C or lower, more preferably 150°C or higher and 250°C or lower.

[0050] In this embodiment, the metal exchange reaction between Cu and Zn proceeds quantitatively, and it is preferable that the precursor Cu is not contained in the nanocrystal. If the precursor Cu remains in the nanocrystal, it acts as a dopant and emits light by a different emission mechanism, widening the fluorescence half-width. The amount of this remaining Cu is preferably 100 ppm or less, more preferably 50 ppm or less, and ideally 10 ppm or less relative to Zn.

[0051] In this embodiment, the ZnSe quantum dots synthesized by the cation exchange method tend to have a higher Cu residual amount than the ZnSe quantum dots synthesized by the direct method, but good luminescence characteristics can be obtained even if the Cu content is about 1 to 10 ppm relative to Zn. It is possible to determine whether the quantum dots are synthesized by the cation exchange method based on the Cu residual amount. That is, by synthesizing by the cation exchange method, the particle size can be controlled with the copper chalcogenide precursor, and a synthesis method that is inherently difficult to react can be made possible, so the Cu residual amount is advantageous in determining whether the cation exchange method has been used.

[0052] Furthermore, in this embodiment, when metal exchange is carried out, a compound is needed that has an auxiliary role of liberating the metal of the copper chalcogenide precursor into the reaction solution by coordination or chelation or the like.

[0053] Compounds having the above-mentioned role include ligands capable of forming a complex with Cu. For example, phosphorus-based ligands, amine-based ligands, and sulfur-based ligands are preferred, and among these, phosphorus-based ligands are more preferred due to their high efficiency.

[0054] This allows the metal exchange between Cu and Zn to be properly performed, and quantum dots with narrow fluorescence half-widths based on Zn and Se can be produced. In this embodiment, the cation exchange method described above allows the mass production of quantum dots compared to the direct synthesis method.

[0055] In the direct synthesis method, in order to increase the reactivity of the Zn raw material, for example, diethyl zinc (Et 2 Zn) is used. However, diethylzinc is highly reactive and flammable in air, so it must be handled under an inert gas flow, making it difficult to handle and store the raw material, and reactions using it are also risky, such as generating heat and catching fire, making it unsuitable for mass production. Similarly, in order to increase the reactivity of the Se raw material, for example, selenium hydride (H 2 Reactions using Se are also not suitable for mass production due to toxicity and safety reasons.

[0056] Furthermore, in reaction systems using highly reactive Zn and Se raw materials as described above, ZnSe is produced, but particle generation is not controlled, resulting in a broad fluorescence half-width of the resulting ZnSe.

[0057] In contrast, in this embodiment, a copper chalcogenide precursor is synthesized from an organic copper compound or an inorganic copper compound and an organic chalcogen compound, and quantum dots are synthesized by metal exchange using the copper chalcogenide precursor. In this way, in this embodiment, quantum dots are synthesized first through the synthesis of a copper chalcogenide precursor, and are not directly synthesized. By such indirect synthesis, it is not necessary to use a reagent that is too highly reactive and dangerous to handle, and it is possible to safely and stably synthesize ZnSe-based quantum dots with narrow fluorescence half-width.

[0058] In this embodiment, it is possible to obtain quantum dots having a desired composition and particle size by performing metal exchange between Cu and Zn in one pot without isolating and purifying the copper chalcogenide precursor. On the other hand, the copper chalcogenide precursor may be used after being isolated and purified once. Furthermore, in this embodiment, the synthesized quantum dots exhibit fluorescent properties without undergoing various treatments such as washing, isolation and purification, coating treatment, and ligand exchange.

[0059] <Shell synthesis method> The method for synthesizing the shell will be described with reference to the flow chart shown in FIG. 4. In this embodiment, for example, after synthesizing a ZnSe core, the surface of the ZnSe core is coated with, for example, ZnSeS. For coating with ZnSeS, for example, a mixture of a Se-TOP solution, an S-TOP solution, and zinc oleate is added to a solution in which the ZnSe core is dispersed, and the mixture is heated at a predetermined temperature while being stirred. By repeating this operation multiple times, the surface of ZnSe can be coated with ZnSeS.

[0060] In this embodiment, after washing, ZnSe / ZnSeS is dispersed in, for example, octadecene (ODE), and trioctylphosphine (TOP) and oleic acid are further added, followed by stirring and heating under predetermined heat treatment conditions (for example, 320° C.×10 min).

[0061] Next, in this embodiment, the ZnS shell is coated. In this embodiment, it is preferable to perform the process of coating the ZnS shell at least in two parts. First, in the first part of the process of coating the ZnS shell, a shell source mixture (shell raw material) containing an acidic compound is added to the solution in which ZnSe / ZnSeS is dispersed. Specifically, zinc oleate (Zn(OLAc) 2 ) solution, dodecanethiol (DDT) and TOP are added, and further, an acidic oxide is added. In this embodiment, the shell source mixed solution containing this acidic oxide is added, and heated under predetermined heating conditions while stirring. The predetermined heating conditions are, for example, a heating temperature of 320°C and a heating time of 10 minutes. In this embodiment, the operation of adding the shell source mixed solution and heating is repeated multiple times. Although FIG. 4 shows that the number of repeated operations is 10 times, "10 times" is an example and does not limit the number of times. However, it is preferable to specify the number of repeated times within the range of about 5 times to 15 times. Thereafter, the mixture is cooled to room temperature.

[0062] In this embodiment, in the first half of the shell coating process, an acidic compound is added to the shell source mixed solution, but a zinc halide compound to be mixed in the second half of the shell coating process is not added. It is known that adding a zinc halide compound to the shell source mixed solution in the first half of the shell coating process reduces the QY. Therefore, in the first half of the shell coating process, a zinc halide compound is not added to the shell source mixed solution.

[0063] Next, in this embodiment, the latter shell coating process is performed. In the latter shell coating process, a shell source mixture containing an acidic compound and a zinc halide compound is added to the solution in which ZnSe / ZnSeS / ZnS is dispersed. This shell source mixture contains, for example, zinc oleate (Zn(OLAc) 2) solution, dodecanethiol (DDT), and TOP, as well as a zinc halide compound and an acidic compound. Thus, in the latter shell coating step, a shell source mixed solution containing an acidic compound and a zinc halide compound is added, and heated under a predetermined heating condition while stirring. The predetermined heating condition is, for example, a heating temperature of 320°C and a heating time of 10 minutes. In this embodiment, the operation of adding the shell source mixed solution and heating is repeated multiple times. Although FIG. 4 shows that the number of repeated operations is 10 times, "10 times" is an example and does not limit the number of times. However, it is preferable to specify the number of repeated operations within a range of about 5 to 15 times.

[0064] The mixture is then cooled to room temperature, washed, and dispersed by addition of ODE. The process from addition of the shell source mixture to dispersion with ODE is repeated until a desired shell thickness is achieved. Thus, the latter shell coating step is characterized by adding a shell source mixed solution containing an acidic compound and a zinc halide compound.

[0065] In this embodiment, the EQE is improved, but in order to achieve this, it is necessary to improve the QY and further optimize the particle shape. If the QY can be increased, the EQE can be improved as shown in (Formula 1).

[0066] The optimization of the particle shape is explained as follows. That is, if the distance between the cores of the quantum dots is short, Förster resonance energy (FRET) occurs, which leads to a decrease in EQE. For this reason, it is considered that by forming a core-shell structure in which the shell is coated around the core, the cores can be physically separated from each other and FRET can be reduced. However, when the shell thickness is increased, the particle shape deteriorates and the QY decreases accordingly. In addition, in the past, there was a problem that the shell could not be coated with a predetermined thickness over the entire surface of the core, resulting in defects, or the shell thickness becomes locally thick, resulting in a deterioration of the particle shape. As a result, it was not possible to appropriately reduce FRET, and the EQE could not be effectively reduced.

[0067] Therefore, in this embodiment, the zinc halide compound is added to the core in small amounts to improve the QY. In particular, the zinc halide compound is not added to the first half of the shell coating process, but is added only to the second half of the shell coating process, so that the QY can be effectively improved. In addition, if the shell source mixture is continuously added, the particle shape deteriorates, so that the shell part with a large thickness is etched locally by adding an acidic compound to the shell source mixture, and the shape is adjusted, and the cross section can be uniformed to a good particle shape with a polygonal shape.

[0068] In this embodiment, the zinc halide compound is added in an amount of about 0.5 mol % to 3 mol %, and more preferably about 1 mol % to 2 mol %, based on the zinc oleate.

[0069] In this embodiment, the acidic compounds include hydrogen chloride (HCl), hydrogen bromide (HBr), hydrogen iodide (HI), trifluoroacetic acid (TFA), trifluoromethanesulfonic acid (TfOH), acetic acid (AA), sulfuric acid (H 2 SO 4 ), phosphoric acid (H 3 PO 4 ) and the like. Among these, it is preferable to use at least one of hydrogen chloride (HCl), hydrogen bromide (HBr), and trifluoroacetic acid (TFA). A high QY can be obtained, and the particle shape of the quantum dots can be improved. In this embodiment, for example, a hydrogen oxide-ethyl acetate solution can be added to the shell source mixture.

[0070] In this embodiment, the zinc halide compound is zinc chloride (ZnCl 2 ), or zinc bromide (ZnBr 2 ), zinc fluoride (ZnF 2 ), zinc iodide (ZnI 2 In this embodiment, for example, a zinc chloride-TOP·oleic acid solution can be added to the shell source mixture. In the present embodiment, the S raw material used for the core-shell structure is not particularly limited, but the following raw materials are typical examples.

[0071] That is, as a thiol, octadecanethiol: C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C 8 H 17 SH, benzenethiol: C 6 H 5 Examples of the sulfur-dissolved solvent that can be used include SH, or a solution of sulfur dissolved in a high-boiling solvent such as a long-chain phosphine-based hydrocarbon, such as trioctylphosphine (S-TOP), a solution of sulfur dissolved in a high-boiling solvent such as a long-chain hydrocarbon, such as octadecene (S-ODE), or a solution of sulfur dissolved in a mixture of oleylamine and dodecanethiol (S-DDT / OLAm).

[0072] Depending on the S raw material used, the reactivity differs, and as a result, the coating thickness of the shell 5b (e.g., ZnS) can be varied. The reactivity of the thiol system is proportional to its decomposition rate, and the reactivity of S-TOP or S-ODE changes in proportion to its stability. Thus, by using different S raw materials, it is possible to control the coating thickness of the shell 5b, and the final fluorescence quantum yield can also be controlled.

[0073] In this embodiment, the less the amine-based solvent used in coating the shell 5b, the easier it is to coat the shell 5b and the better the luminescence characteristics can be obtained. Furthermore, the luminescence characteristics after coating the shell 5b differ depending on the ratio of the amine-based solvent to the carboxylic acid-based or phosphine-based solvent.

[0074] Furthermore, the quantum dots 5 synthesized by the manufacturing method of this embodiment can be aggregated by adding a polar solvent such as methanol, ethanol, or acetone, and the quantum dots 5 and unreacted raw materials can be separated and collected. The collected quantum dots 5 are dispersed again by adding toluene, hexane, or the like. By adding a solvent that serves as a ligand to this redispersed solution, it is possible to further improve the luminescence characteristics and improve the stability of the luminescence characteristics. The change in the luminescence characteristics caused by adding this ligand is greatly different depending on whether or not the shell 5b is coated, and in this embodiment, the quantum dots 5 coated with the shell 5b can be improved in particular in fluorescence stability by adding a thiol-based ligand.

[0075] The applications of the quantum dots 5 shown in FIGS. 1A and 1B are not particularly limited. For example, the quantum dots 5 of this embodiment that emit blue fluorescence can be applied to wavelength conversion members, lighting members, backlight devices, display devices, and the like.

[0076] The quantum dots 5 of this embodiment are applied to a wavelength conversion member, an illumination member, a backlight device, a display device, etc., and when photoluminescence (PL) is used as the light emission principle, blue fluorescence can be emitted by UV irradiation from a light source. Alternatively, when electroluminescence (EL) is used as the light emission principle, or when quantum dots emit all three primary colors by other methods, the quantum dots 5 of this embodiment can be used as a light emitting element that emits blue fluorescence. In this embodiment, a light emitting element (full color LED) including quantum dots 5 of this embodiment that emit blue fluorescence, together with quantum dots that emit green fluorescence and quantum dots that emit red fluorescence, can be used to emit white light.

[0077] Fig. 2 is a schematic diagram of an LED device using quantum dots according to this embodiment. As shown in Fig. 2, the LED device 1 according to this embodiment is configured to include a storage case 2 having a bottom surface 2a and a side wall 2b surrounding the bottom surface 2a, an LED chip (light-emitting element) 3 arranged on the bottom surface 2a of the storage case 2, and a fluorescent layer 4 filled in the storage case 2 and sealing the upper surface side of the LED chip 3. Here, the upper surface side refers to the direction in which light emitted by the LED chip 3 is emitted from the storage case 2, and indicates the opposite direction to the bottom surface 2a with respect to the LED chip 3.

[0078] The LED chip 3 is disposed on a base wiring board (not shown), which may constitute the bottom surface of the storage case 2. The base board may be, for example, a base material such as glass epoxy resin having a wiring pattern formed thereon. The LED chip 3 is a semiconductor element that emits light when a voltage is applied in the forward direction, and has a basic configuration in which a P-type semiconductor layer and an N-type semiconductor layer are PN junctioned. As shown in FIG. 2, the fluorescent layer 4 is formed from a resin 6 in which a large number of quantum dots 5 are dispersed.

[0079] The resin composition in this embodiment in which the quantum dots 5 are dispersed may contain the quantum dots 5 and a fluorescent material other than the quantum dots 5. The fluorescent material may be a sialon-based material or a KSF (K 2 SiF 6 :Mn 4+ ) red phosphor, but the material is not particularly limited.

[0080] The resin 6 constituting the fluorescent layer 4 is not particularly limited, but examples of the resin that can be used include polypropylene (PP), polystyrene (PS), acrylic resin, methacrylic resin, MS resin, polyvinyl chloride (PVC), polycarbonate (PC), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polymethylpentene, liquid crystal polymer, epoxy resin, silicone resin, and mixtures of these.

[0081] The LED device using the quantum dots of this embodiment can be applied to a display device. Fig. 3 is a vertical cross-sectional view of a display device using the LED device shown in Fig. 2. As shown in Fig. 3, a display device 50 is configured to have a plurality of LED devices 20 and a display unit 54 such as a liquid crystal display facing each LED device 20. Each LED device 20 is disposed on the back side of the display unit 54. Each LED device 20 has a structure in which an LED chip is sealed with a resin in which a large number of quantum dots 5 are diffused, similar to the LED device 1 shown in Fig. 2.

[0082] As shown in Fig. 3, the LED devices 20 are supported by a support 52. The LED devices 20 are arranged at predetermined intervals. The LED devices 20 and the support 52 constitute a backlight 55 for a display unit 54. The support 52 is not particularly limited in shape or material and may be in the form of a sheet, plate, or case. As shown in Fig. 3, a light diffusion plate 53 or the like may be interposed between the backlight 55 and the display unit 54.

[0083] By applying the quantum dots 5 of this embodiment to the LED device shown in Fig. 2 or the display device shown in Fig. 3, it is possible to effectively improve the light emitting characteristics of the device. In particular, it is possible to improve the EQE when the quantum dots of this embodiment are applied to a QLED element. In this embodiment, an EQE of 7% or more can be obtained, preferably 9% or more, more preferably 10% or more, and even more preferably 10.5% or more.

[0084] Furthermore, a resin composition in which the quantum dots 5 of this embodiment are dispersed in a resin can be formed into a sheet or film. Such a sheet or film can be incorporated into, for example, a backlight device.

[0085] In addition, in this embodiment, a wavelength conversion member in which a plurality of quantum dots are dispersed in a resin can be formed by a molded body. For example, a molded body in which quantum dots are dispersed in a resin is stored in a container having a storage space by pressing or the like. At this time, it is preferable that the refractive index of the molded body is smaller than the refractive index of the container. As a result, a part of the light that enters the molded body is totally reflected by the inner wall of the container. Therefore, it is possible to reduce the beam of light leaking from the side of the container to the outside. In this way, by applying the quantum dots in this embodiment to wavelength conversion members, lighting members, backlight devices, display devices, and the like, it is possible to effectively improve the light emission characteristics. EXAMPLES

[0086] The effects of the present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0087] In the present invention, the following raw materials were used to synthesize the Cd-free blue fluorescent quantum dots, and the following measuring instruments were used to evaluate the synthesized quantum dots. <Raw materials> Anhydrous copper acetate: Wako Pure Chemical Industries, Ltd. Octadecene: Manufactured by Idemitsu Kosan Co., Ltd. Oleylamine: Farmin, manufactured by Kao Corporation Oleic acid: Luna O-V manufactured by Kao Corporation Dodecanethiol (DDT): Thiocol 20 manufactured by Kao Corporation Trioctylphosphine (TOP): manufactured by Hokko Chemical Industry Co., Ltd. Zinc acetate anhydride: manufactured by Kishida Chemical Co., Ltd. Selenium (4N: 99.99%): manufactured by Shinsei Chemical Co., Ltd. Sulfur: manufactured by Kishida Chemical Co., Ltd. Hydrogen chloride: manufactured by Kokusan Chemical Co., Ltd. Zinc chloride: manufactured by Kanto Chemical Co., Inc. Hydrogen bromide: manufactured by Tokyo Chemical Industry Co., Ltd. Zinc bromide: manufactured by Kishida Chemical Co., Ltd. <Measuring Instruments> Fluorescence spectrometer: F-2700 manufactured by JASCO Corporation UV-visible spectrophotometer: V-770 manufactured by Hitachi, Ltd. Fluorescence quantum yield measurement device: QE-1100 manufactured by Otsuka Electronics Co., Ltd. X-ray diffractometer (XRD): D2 PHASER manufactured by Bruker Scanning electron microscope (SEM): SU9000 manufactured by Hitachi, Ltd. Fluorescence lifetime measurement device: C11367 manufactured by Hamamatsu Photonics LED measurement device: manufactured by Spectra-Physics Transmission electron microscope (TEM): JEM-ARM200-CF manufactured by JEOL Ltd. XEDS detector: JED2300T manufactured by JEOL Ltd.

[0088] [Example 1] <Synthesis method of ZnSe core> 728 mg of copper acetate anhydride: Cu(OAc) and 19.2 mL of oleylamine: OLAm and 31 mL of octadecene: ODE were placed in a 300 mL reaction vessel. Then, under an inert gas (N 2 ) atmosphere, it was heated with stirring at 165 °C for 20 minutes to dissolve the raw materials. 2

[0089] ​To this solution, 4.56 mL of Se-DDT / OLAm solution (0.7 M) was added, and the mixture was heated with stirring at 165 °C for 30 minutes. The resulting reaction solution (CuSe) was cooled to room temperature.

[0090] After that, to the CuSe reaction solution, zinc acetate anhydrous: Zn(OAc) 2 7376 mg, trioctylphosphine: TOP 40 mL, and oleylamine: OLAm 1.6 mL were added, and the mixture was heated with stirring at 200 °C for 1 hour under an inert gas (N 2 ) atmosphere. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0091] Ethanol was added to the reaction solution cooled to room temperature to cause precipitation, and the precipitate was collected by centrifugation. Then, 96 ml of octadecene: ODE was added to the precipitate to disperse it.

[0092] After that, to 96 ml of the ZnSe-ODE solution, zinc acetate anhydrous: Zn(OAc) 2 7376 mg, trioctylphosphine: TOP 40 mL, oleylamine: OLAm 4 mL, and oleic acid: OLAc 24 mL were added, and the mixture was heated with stirring at 290 °C for 30 minutes under an inert gas (N 2 ) atmosphere. The resulting reaction solution (ZnSe) was cooled to room temperature. The resulting reaction solution was measured with a fluorescence spectrometer. As a result, optical properties with a fluorescence wavelength of about 446.5 nm and a fluorescence half-width of about 14 nm were obtained.

[0093] <Method for coating a shell on a ZnSe core> Ethanol was added to 40 ml of the ZnSe reaction solution to cause precipitation, and the precipitate was collected by centrifugation. Then, 35 ml of octadecene: ODE was added to the precipitate to disperse it.

[0094] To 35 mL of the dispersed ZnSe-ODE solution, 2 mL of oleic acid: OLAc and 4 mL of trioctylphosphine: TOP were added, and the mixture was heated with stirring at 320 °C for 10 minutes under an inert gas (N 2 ) atmosphere.

[0095] To this solution, add 0.5 mL of Se-TOP solution (1M), 0.5 mL of S-TOP solution (1M), and zinc oleate (Zn(OLAc) 2 0.9 mL of the mixture of 5 mL of solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated four times.

[0096] Then, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 35 ml of octadecene (ODE) was added to the precipitate to disperse it. Then, 2 mL of oleic acid (OLAc) and 4 mL of trioctylphosphine (TOP) were added in the same manner as before, and an inert gas (N 2 ) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0097] To this solution, add 0.4 mL of DDT, 1.6 mL of trioctylphosphine (TOP), 0.12 mL of hydrogen chloride-ethyl acetate solution (4 M), and zinc oleate (Zn(OLAc) 2 0.9 mL of the mixture of 10 mL of solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated 10 times.

[0098] Then, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 35 ml of octadecene (ODE) was added to the precipitate to disperse it. Then, 2 mL of oleic acid (OLAc) and 4 mL of trioctylphosphine (TOP) were added in the same manner as before, and an inert gas (N 2 ) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0099] To this solution, add 0.4 mL of DDT, 1.6 mL of trioctylphosphine:TOP, 0.12 mL of hydrogen chloride-ethyl acetate solution (4 M), 0.1 mL of zinc chloride-TOP·oleic acid solution (0.8 M), and zinc oleate:Zn(OLAc) 2 0.9 mL of the mixture of 10 mL of solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated 10 times.

[0100] Then, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 35 ml of octadecene (ODE) was added to the precipitate to disperse it. Then, 2 mL of oleic acid (OLAc) and 4 mL of trioctylphosphine (TOP) were added in the same manner as before, and an inert gas (N 2 ) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0101] To this solution, add 0.4 mL of DDT, 1.6 mL of trioctylphosphine:TOP, 0.2 mL of hydrogen chloride-ethyl acetate solution (4 M), 0.1 mL of zinc chloride-TOP·oleic acid solution (0.8 M), and zinc oleate:Zn(OLAc) 2 0.9 mL of the mixture of 10 mL of solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated 10 times. The resulting reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were as shown in FIG. 5, with a fluorescence wavelength of about 442 nm and a fluorescence half-width of about 15 nm. Ethanol was added to the obtained reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to the precipitate to disperse it. The obtained dispersion solution was measured with a UV-Vis spectrometer. As a result, the UV-Vis absorption spectrum shown in FIG. 6 was obtained. FIG. 7 shows the X-ray diffraction (XRD) spectrum of Example 1. From the results in FIG. 7, crystal peaks of cubic crystals consisting of Zn, Se, and S could be confirmed.

[0102] <Measurement results> ZnSe / ZnSeS / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was approximately 96%. The fluorescence lifetime was measured and found to be 16 ns. Elemental analysis (EDX) showed the following: Zn: 42 atom%, Se: 11 atom%, S: 41 atom%, Cl: 1 atom%. Analysis of the TEM image showed that the shell thickness was 2.0 nm. Moreover, by using the quantum dots obtained in Example 1, a light-emitting device having the following layered structure was manufactured. ITO / PEDOT:PSS / PVK / QD layer / LiZnO / Al When this device was evaluated using an LED measuring device, the maximum external quantum efficiency (EQE) was 18.6%.

[0103] [Example 2] The synthesis was carried out under the same conditions as in Example 1, except that the zinc chloride-TOP·oleic acid solution used in Example 1 was changed to a zinc bromide-TOP·oleic acid solution. [Example 3] The synthesis was carried out under the same conditions as in Example 2, except that the hydrogen chloride-ethyl acetate solution (4 M) used in Example 2 (see the description in Example 1) was changed to a hydrogen bromide-acetic acid solution. [Example 4] The synthesis was carried out under the same conditions as in Example 1, except that the hydrogen chloride-ethyl acetate solution (4 M) used in Example 1 was changed to trifluoroacetic acid. [Example 5] The synthesis was carried out under the same conditions as in Example 2, except that the hydrogen chloride-ethyl acetate solution (4 M) (see the description in Example 1) used in Example 2 was changed to trifluoroacetic acid.

[0104] 8 is a table summarizing the measurement results of Examples 1 to 5. In addition, TEM photographs of the quantum dots obtained in Examples 1 to 5 are also shown. 8, the EQE was able to be 7% or more in all of Examples 1 to 5. In particular, in Example 1, the EQE was able to be improved to 18.6%. In addition, in all of the examples, the QY was 70% or more. In particular, in Example 2, the QY was improved to 98%.

[0105] In each example, the fluorescence half-width was 20 nm or less. Furthermore, in each example, the fluorescence wavelength was within the range of 410 nm to 470 nm, and blue fluorescence was observed. The shell thickness in each example was in the range of about 2 nm to 2.5 nm. The shell thickness can be estimated from a photograph of the TEM-EDX analysis results.

[0106] As shown in the SEM photographs of each example in FIG. 8, it was found that the particle shape of the quantum dots was substantially rectangular (substantially cubic) and good. That is, it is considered that the ZnSe core crystallized into a substantially rectangular shape, and a shell with a predetermined thickness was coated over its entire circumference, thereby maintaining the substantially rectangular particle shape. This is presumably because the addition of an acidic compound to the shell source mixture had the effect of etching the portions where the particle shape deteriorated.

[0107] [Example 6] Among the synthesis steps used in Example 1, the <synthesis method of ZnSe core> was the same, and a part of the <coating method of the shell on the ZnSe core> was changed to synthesize quantum dots. Hereinafter, the <coating method of the shell on the ZnSe core> of Example 6 will be described.

[0108] <Coating method of the shell on the ZnSe core> Ethanol was added to 40 ml of the ZnSe reaction solution to generate a precipitate, and the precipitate was collected by centrifugation. 35 ml of octadecene: ODE was added to the precipitate and dispersed.

[0109] To 35 mL of the dispersed ZnSe-ODE solution, 2 mL of oleic acid: OLAc and 4 mL of trioctylphosphine: TOP were added, and heated with stirring at 320 ° C for 10 minutes under an inert gas (N 2 ) atmosphere.

[0110] To this solution, 0.9 mL of a mixed solution of 0.5 mL of Se-TOP solution (1 M), 0.5 mL of S-TOP solution (1 M), and 5 mL of zinc oleate: Zn(OLAc) 2 solution (0.4 M) was added, and heated with stirring at 320 ° C for 10 minutes. This operation was repeated 4 times.

[0111] Then, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 35 ml of octadecene (ODE) was added to the precipitate to disperse it. Then, 2 mL of oleic acid (OLAc) and 4 mL of trioctylphosphine (TOP) were added in the same manner as before, and an inert gas (N 2 ) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0112] To this solution, add 0.6 mL of DDT, 1.4 mL of trioctylphosphine (TOP), 0.24 mL of hydrogen chloride-ethyl acetate solution (4 M), and zinc oleate (Zn(OLAc) 2 0.9 mL of the mixture of 10 mL of solution (0.48 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated 10 times.

[0113] Then, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 35 ml of octadecene (ODE) was added to the precipitate to disperse it. Then, 2 mL of oleic acid (OLAc) and 4 mL of trioctylphosphine (TOP) were added in the same manner as before, and an inert gas (N 2 ) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0114] To this solution, add 0.6 mL of DDT, 1.4 mL of trioctylphosphine:TOP, 0.24 mL of hydrogen chloride-ethyl acetate solution (4 M), 0.1 mL of zinc chloride-TOP·oleic acid solution (0.8 M), and zinc oleate:Zn(OLAc) 2 0.9 mL of the mixture of 10 mL of solution (0.48 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated 10 times.

[0115] <Measurement Results of Example 6> ZnSe / ZnSeS / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was approximately 90%. The fluorescence lifetime was measured and found to be 20 ns. The shell thickness was found to be 2.7 nm by analyzing the TEM images.

[0116] [Example 7] The <synthesis method of ZnSe core> and <coating method of shell on ZnSe core> of Example 1 were used as they were. Finally, 2.0 mL of zinc chloride-TOP zinc chloride-TOP·oleic acid solution (0.8 M) was added, and it was heated while stirring for 20 minutes. <Measurement Results of Example 7> Hexane-dispersed ZnSe / ZnSeS / ZnS was measured with a quantum efficiency measurement system. As a result, the fluorescence quantum yield was about 84%. Also, as a result of measuring the fluorescence lifetime, it was 25 ns. As a result of elemental analysis (EDX), it was Zn: 32 atom%, Se: 12 atom%, S: 50 atom%, Cl: 6 atom%. As a result of analyzing the image obtained by TEM, the thickness of the shell was 2.0 nm.

[0117] In Example 6, the shell was made thicker than in Example 1 in order to more effectively prevent Förster resonance energy transfer (FRET). Specifically, while the shell thickness of Example 1 was 2 nm, in Example 6, the shell thickness was increased to 2.7 nm. Also, in Example 6, it was possible to suppress the decrease in fluorescence quantum yield (QY) as much as possible compared to Example 1.

[0118] In Example 7, the chlorine content was increased for the purpose of reducing Zn without ligands on the surface of the quantum dots. That is, while the Cl content of Example 1 was 1 atom%, the Cl content of Example 7 was 6 atom%. [Comparative Example 1] Comparative Example 1 is an example in which the shell was coated without mixing an acidic compound and a zinc halide compound in the shell source mixture. Specifically, the shell was coated by the following steps.

[0119] 182 mg of copper acetate anhydrous: Cu(OAc) 2 and 4.8 mL of oleylamine: OLAm and 7.75 mL of octadecene: ODE were placed in a 100 mL reaction vessel. Then, under an inert gas (N 2 ) atmosphere, it was heated with stirring at 165 °C for 5 minutes to dissolve the raw materials.

[0120] To this solution, 1.14 mL of a Se-DDT / OLAm solution (0.7 M) was added, and the mixture was heated with stirring at 165° C. for 30 minutes. The resulting reaction solution (CuSe) was cooled to room temperature.

[0121] Then, Cu 2 In the Se reaction solution, anhydrous zinc acetate: Zn(OAc) 2 Add 1844 mg of the solution, 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm), and place in an inert gas (N 2 ) atmosphere, and heated at 180° C. for 45 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0122] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0123] Then, 12 ml of the ZnSe-ODE solution was added to anhydrous zinc acetate: Zn(OAc) 2 Add 1844 mg of trioctylphosphine (TOP) (10 mL), oleylamine (OLAm) (1 mL), and oleic acid (OLAc) (6 mL) to the flask and purify with an inert gas (N 2 ) atmosphere, and heated at 280° C. for 20 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0124] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 447.5 nm and a fluorescence half-width of about 14 nm.

[0125] Ethanol was added to 20 ml of the resulting ZnSe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene (ODE) was added to disperse the precipitate.

[0126] Add 1 mL of oleic acid (OLAc) and 2 mL of trioctylphosphine (TOP) to 17.5 mL of the dispersed ZnSe-ODE solution and place in an inert gas (N 2) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0127] To this solution, add 0.5 mL of Se-TOP solution (1M), 0.125 mL of DDT, 0.375 mL of trioctylphosphine (TOP), and zinc oleate (Zn(OLAc) 2 0.5 mL of the mixture of 5 mL of solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated four times.

[0128] After that, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate. 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it, and 1 ml of oleic acid (OLAc) and 2 ml of trioctylphosphine (TOP) were added in the same manner as above, and an inert gas (N 2 ) atmosphere, and the mixture was heated at 320° C. for 10 minutes with stirring.

[0129] To this solution, add 0.5 mL of DDT, 1.5 mL of trioctylphosphine (TOP), and zinc oleate (Zn(OLAc) 2 0.5 mL of the mixture of 10 mL of solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated 10 times.

[0130] Thereafter, ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it (washing step).

[0131] Next, add 1 mL of oleic acid (OLAc) and 2 mL of trioctylphosphine (TOP) in the same manner as before, and then fill the flask with inert gas (N 2 The solution was heated at 320° C. for 10 minutes under stirring in a 100% aqueous solution of 1,000 mM NaOH. To this solution, 0.5 mL of DDT, 1.5 mL of trioctylphosphine (TOP), and zinc oleate (Zn(OLAc) 20.5 mL of the mixture of 10 mL of the solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes while stirring. This operation was repeated six times. Then, the mixture was heated at 320° C. for 30 minutes while stirring (shell coating process).

[0132] Thereafter, the reaction solution was subjected to the above-mentioned (washing step) and (shell coating step) operations three times to finally obtain the target reaction solution (ZnSe / ZnS), which was then cooled to room temperature.

[0133] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 443 nm and a fluorescence half-width of about 15 nm. Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0134] ZnSe / ZnSeS / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was about 60%. The fluorescence lifetime was measured and was 14 ns. Moreover, by using the quantum dots obtained in Comparative Example 1, a light emitting device having the following layered structure was manufactured. ITO / PEDOT:PSS / PVK / QD layer / ZnO / Al When this device was evaluated using an LED measuring device, the maximum external quantum efficiency (EQE) was 4.0%. Below, Example 1 is compared with Comparative Example 1. Table 1 shows the measurement results of Example 1 and Comparative Example 1.

[0135] [Table 1]

[0136] It was found that Comparative Example 1 had a lower EQE than Example 1. Fig. 9A is a photograph of the TEM-EDX analysis results in Comparative Example 1, and Fig. 9B is a photograph of the TEM-EDX analysis results in Example 1. Fig. 10A is a partial schematic diagram of Fig. 9A, and Fig. 10B is a partial schematic diagram of Fig. 9B.

[0137] As shown in Figures 9A and 9B, the photographs of the TEM-EDX analysis results are shown in three colors (red, blue, and green), and it was found that the center part is mainly a mixture of red and blue, which is almost purple, while the outside is mainly a mixture of red and green, which is almost yellow. Since red indicates Zn, blue indicates Se, and green indicates S, it was found that mainly Zn and Se are present in the center part, and mainly Zn and S are present on the outside. Therefore, it can be inferred from the photographs of the TEM-EDX analysis results shown in Figures 9A and 9B that the core is ZnSe and the shell is ZnS. And, by measuring the thickness of the almost yellow part from the photographs of the TEM-EDX analysis results, the shell thickness can be estimated.

[0138] 9A and 10A, in Comparative Example 1, the shell covering the periphery of the core was not of a uniform thickness, and was broken in places, and there were some parts where the shell had grown locally. Therefore, the particle shape of Comparative Example 1 was deteriorated, Förster resonance energy transfer (FRET) was likely to occur, and the EQE was reduced. In addition, Comparative Example 1 did not obtain a QY as high as Example 1.

[0139] In contrast, in Example 1, as shown in Figures 9B and 10B, the shell neatly covered the entire circumference of the core, the shell had a substantially constant thickness, and the particle shape of the quantum dot was substantially rectangular. Thus, the particle shape of Example 1 was better than that of Comparative Example 1, and a sufficiently higher QY than that of Comparative Example 1 could be obtained. As a result, Example 1 was able to obtain a sufficiently higher EQE than that of Comparative Example 1. [Industrial Applicability]

[0140] According to the present invention, quantum dots that emit blue fluorescence can be stably obtained. By applying the quantum dots of the present invention to LEDs, backlight devices, display devices, etc., excellent light emission characteristics can be obtained in each device. [Explanation of symbols]

[0141] 1:LED device 2: Storage case 3: LED chip 4: Fluorescent layer 5: Quantum dots 5a: Core 5b: Shell 11:Organic ligand 50:Display device 52:Support 53: Light diffusion plate 54:Display section 55: Backlight

Claims

1. A core-shell quantum dot, The shell has an intermediate layer and an outermost layer, the intermediate layer is located between the core and the outermost layer, the intermediate layer comprises ZnSeS; Contains a halogen element, A quantum dot characterized by:

2. At least an external quantum efficiency of 7% or more, or a fluorescence quantum yield of 70% or more; The quantum dot according to claim 1 .

3. The halogen element is detected by elemental analysis using energy dispersive X-ray analysis, and the content of the halogen element is 0.01 atom % to 5 atom %. The quantum dot according to claim 1 or 2.

4. The halogen element is chlorine or bromine. The quantum dot according to any one of claims 1 to 3.

5. Contains Cu, The quantum dot according to any one of claims 1 to 4.

6. A method for producing a core-shell quantum dot, comprising the steps of: The shell has an intermediate layer and an outermost layer, the intermediate layer is located between the core and the outermost layer, The step of generating the shell comprises: coating the core with ZnSeS as the intermediate layer; comprising a step of blending an acidic compound and a zinc halide compound in the outermost layer, The present invention relates to a method for producing quantum dots.

7. The step of coating the outermost layer is divided into at least a first half and a second half, In the first half, the acidic compound is blended, but the zinc halide compound is not blended; In the latter half, a step of mixing both an acidic compound and a zinc halide compound is performed. The method for producing quantum dots according to claim 6, further comprising:

8. 8. The method for producing quantum dots according to claim 6, wherein at least one of hydrogen chloride, hydrogen bromide, and trifluoroacetic acid is used as the acidic compound.

9. 9. The method for producing quantum dots according to claim 6, wherein at least one of zinc chloride and zinc bromide is used as the zinc halide compound.

Citation Information

Patent Citations

  • High-brightness nanostructures and methods for producing them

    JP2015529698A

  • Quantum dot, wavelength conversion member using quantum dot, illumination member, backlight device, display device and method for manufacturing quantum dot

    JP2020041124A

  • Quantum dots and devices including the same

    US20170179338A1

  • Methods to improve the quantum yield of indium phosphide quantum dots

    US20200325396A1

  • Quantum dot material and method for manufacturing same

    WO2017188300A1